Andrological Aspects of Exercise: Moderate Swimming Protects against Isoproterenol Induced Testis and Semen Abnormalities in Rats - Péter Osváth; Miklós Szűcs; Denise Börzsei; Renáta Szabó; Zelma Nadin Lesi; Zsolt Turcsán; Médea Veszelka; Judith Sebestyén; Béla Juhász; Dániel Priksz; Csaba Varga; Anikó Pósa (MDPI AG, 2022)
The development and progression of male infertility are closely linked to a sedentary lifestyle; however, its underlying mechanisms are not fully elucidated. Our aim was to assess the protective effects of moderate swimming exercise on the male reproductive system in isoproterenol-treated rats. Male Wistar rats were divided into five groups as follows: (1) non-interventional controls (CTRL), (2) isoproterenol-treated (ISO), (3) pre-treatment swimming training + ISO (PRE + ISO), (4) ISO + post-treatment swimming training (ISO+POST), (5) pre-treatment swimming training + ISO + post-treatment swimming training (PRE + ISO + POST) groups. Testicular oxidative stress was induced by ISO injection (1.0 mg/kg). Rats in the pre- or post-training groups were trained five days a week. At the end of the experimental period, serum testosterone levels, sperms' hyaluronan binding, and total glutathione (GSH) content, as well as myeloperoxidase activity (MPO), TNF alpha and IL6 concentrations in the testis and semen, were measured. Serum testosterone levels, sperms' hyaluronan binding, and GSH content were found to be significantly reduced, while MPO, TNF alpha and IL6 concentrations in the testis and semen were elevated after the ISO treatment compared to the CTRL group. Moderate-intensity swimming exercise effectively alleviated the negative effects of high oxidative stress. Our findings provide the first evidence that moderate-intensity swimming exercise confers sustained protection from isoproterenol-induced adverse effects on testicular inflammation.